âKewirausahaan Muslimâ - Prihatna, Nana (Manajemen Bisnis Syariah, 2010)
The work and effort include entrepreneurship and can be part and parcel of human life because its existence as a caliph in this world is meant to prosper the earth and bring it to a better direction (Surah 11/Hud: 61). Poor condition due to tradition and understanding of the country is finally making children less touch of entrepreneurship, the development and growth of entrepreneurial spirit is a task that inhern in religion, and also is one alternative for the recovery of economic crisis and employment which still wrapped around our nation. Why entrepreneurship needs to be developed in Indonesia, with a majority Moslem population, the reality of a number of existing labor force is still not much accommodated in employment, thus opening new jobs become a necessity in empowering of Indonesian. Prophet Muhammad SAW who is a role model for Moslems, the largest community of this country, is a trader who is very tough and professional, honest, holding the trusteeship, and reliable. Credibility and personal integrity even as traders gained recognition, not only from Moslems but also Jews and the Christians, because the Prophet has been in business with very professional. Keywords: entrepreneurship, Moslems, exemplary